Culling pattern in Murrah buffalo males reserved for breeding - Shivahre, Pushp Raj (Indian Journal of Dairy Science, 2014)
Murrah males initially reserved for breeding on the basis of pedigree performance were raised for semen donation; a number of those were culled before reaching the stage of frozen semen production due to various reasons. An attempt was made to identify the pattern of culling and causes thereof at different stages. A total of 244 males out of 1029 males born were reserved for breeding. Over the years (1997-2012) overall percent Murrah buffalo males reserved for breeding was 23.71 %. Average Damâ€™s best 305 days lactation yield was 2879.93 kg for selected vs 2311.45 kg for all the males born. Out of 244 males reserved, number of animals culled in the 0-18 months, 18 months-3 years, 3-5 years and > 5 years; age group categories were 29, 53, 64 and 33 respectively.Â Major causes of culling in age group upto 18 months were surplus (7.38%) followed by poor growth, offbreed and miscellaneous. In age group 18 months-3 years, main reasons of culling were surplus (17.00%) followed by off breed, poor libido and poor growth. For age group 3-5 years, main reasons of culling were surplus (26.71%) and reproductive problems (mainly poor libido) (12.33%). The remaining causes were not of much significance. Period P3 (2005-2008) revealed higher disposal on account of surplus reason. In males of age group above 5 years of age, most of breeding bulls were culled on account of surplus reason (32.93%), as the required numbers of doses of frozen semen were already produced from those bulls. Most of the bulls born during period 2009-12, were not available in this age group.